PENGARUH MEDIA PEMBELAJARAN GAWANG TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA BERJALAN DI UDARA PADA SISWA SMA - Iqbal, Syarif Muhammad; Simanjuntak, Victor G; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The problem in this study wht are the difficulties in learning physical education in children with special needs in Pontianak Special Light Nation Middle School. The purpose of this study is to find out what is the diffuculty of learning physical education for children with special need in Pontianak Special Light Nation Middle School. The research method used in this study is the quantitative method of the object which will be examined as it is or the natural state. The form of research is a survey. Data collection techniques used are using observation and interviews. Data analysis techniques used are percentage descriptive data analysis techniques. The results of the data obtained are percentage in %. The results of the study based on observations showed that 34% of the aspects observed were not carried out by the teacher during the learning process, and 64% of the aspects observed were carried out by the teacher during the learning perocces. From the results of interviews with teachers there were difficulties in learning sports and health physical education activities, namely: difficulties in conveying material, difficulties in sport practice, difficulties in understanding and social interaction. Keywords: Observation, Learning Process